2017
DOI: 10.12688/f1000research.11404.1
|View full text |Cite
|
Sign up to set email alerts
|

Marine archaea and archaeal viruses under global change

Abstract: Global change is altering oceanic temperature, salinity, pH, and oxygen concentration, directly and indirectly influencing marine microbial food web structure and function. As microbes represent >90% of the ocean’s biomass and are major drivers of biogeochemical cycles, understanding their responses to such changes is fundamental for predicting the consequences of global change on ecosystem functioning. Recent findings indicate that marine archaea and archaeal viruses are active and relevant components of mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 88 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, it has been estimated that virus-mediated turnover of archaea in surface deep-sea sediments accounts for up to one-third of the total microbial biomass killed, resulting in the release of ~0.3 to 0.5 gigatons of carbon per year globally (Danovaro et al, 2016). These recent findings greatly expand our appreciation of the diversity of archaeal viruses and illuminate their prominent role in the Biosphere (Danovaro et al, 2017).…”
Section: Archaea and Their Virusesmentioning
confidence: 66%
“…Furthermore, it has been estimated that virus-mediated turnover of archaea in surface deep-sea sediments accounts for up to one-third of the total microbial biomass killed, resulting in the release of ~0.3 to 0.5 gigatons of carbon per year globally (Danovaro et al, 2016). These recent findings greatly expand our appreciation of the diversity of archaeal viruses and illuminate their prominent role in the Biosphere (Danovaro et al, 2017).…”
Section: Archaea and Their Virusesmentioning
confidence: 66%
“…It has been demonstrated that virus‐mediated turnover of thaumarchaea in surface deep‐sea sediments accounts for up to one‐third of the total microbial biomass killed, resulting in the release of approximately 0.3–0.5 gigatons of carbon per year globally and that turnover of thaumarchaea by viruses in the deep ocean is faster than that of bacteria (Danovaro et al ., ). These findings illuminate the prominent role of thaumarchaeal viruses in the Biosphere (Danovaro et al ., ). Despite the importance of thaumarchaea and their viruses in the global nitrogen and carbon cycling (Offre et al ., ), only two proviruses (Krupovic et al ., ; Abby et al ., ) and three casposons (Krupovic et al ., ; Krupovic et al ., ) have been identified in the thaumarchaeal genomes.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, little is known about their viral co-symbionts and their ecological roles across niches within harsh life conditions around the world [ 9 ]. Furthermore, numerous ecological studies have revealed that prokaryotic viruses predominate across different environments, including extreme niches, and outnumbering their hosts by at least an order of magnitude [ 10 , 11 ]. Thus, documenting viral diversity in extremophile hosts, from molecular and taxonomic perspectives, provides vital information about how viruses shaped life on earth and about the viral molecular mechanisms involved in this process, which could constitute a source of novel molecular tools for biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%